The 'lexis' of medieval computus in selected Anglo-Latin and Old English prose - Harris, Anthony (Apollo - University of Cambridge Repository, 2021)
The study of medieval computus (the calculation of the date of Easter) was popular amongst German scholars during the latter part of the nineteenth century, and American and German scholars in the early twentieth. Scholarly interest waned during the mid-late twentieth century, probably because computus is not the easiest subject to study without a firm grounding in mathematics, but the study of the ‘science’ has enjoyed a renaissance in recent years largely driven by the work of scholars at the National University of Galway. This revival is distinguished by the discovery of new computistical folios and manuscripts, an increased understanding of the Irish or ‘Celtic’ computus, significant discoveries of dating clauses by scholars such as Ó Cróinín and Warntjes, and new theories of transmission and dissemination. No study of the vocabulary of computus has presented itself although studies of Latin scientific vocabulary do exist which focus on medicine or natural sciences. Similarly, there are individual studies of vernacular vocabulary for works such as Byrhtferth’s Enchiridion, but these have tended to comprise little more than word lists rather than any detailed analysis of the lexis. Therefore, an opportunity presented itself to enhance scholarly understanding of the vocabulary used by computus specifically and to add to the body of lexicological scholarship in general. This doctoral dissertation has considered the development of the vocabulary of the Roman computus (the science of the calculation of the date of Easter according to the church of Rome) in the fields of arithmetic, astronomy, and theology in selected Latin and Old English texts between the fifth and the twelfth centuries. It has investigated whether the Latin vocabulary of computus underwent significant change as the science developed from Victorius of Aquitaine’s 532-year Cursus Paschalis (c. 457), through to Dionysius Exiguus’ 95-year (5 x 19 year) Easter Table and Argumenta in the sixth century (c. 532), to Bede’s De Temporum Ratione and 532-year Circulus Paschae Magnus (Great Easter Cycle) in the eighth (c. 723). It has also briefly considered later innovations by Abbo and the School at Fleury in the tenth and eleventh centuries respectively and, by way of comparison, studied and compared Ælfric’s and Byrhtferth’s late tenth/early eleventh vernacular computistical language. It has investigated whether the vocabulary of computus employed by Victorius and Dionysius was substantially different to the lexis employed by Bede, Abbo, Ælfric, or Byrhtferth and/or whether a standardised Latin or vernacular vocabulary might have been developed specifically for computus during the period (much as the Winchester vocabulary exists for works of theology). In summary, this research has sought not only to develop a better understanding of how the vocabulary of the Roman computus developed during the period of study but also how early medieval computists might have perceived and utilised the interrelationship between astronomy, theology, and the calculation of time.
Keywords: Anglo-Saxon; English; Old English; Anglo-Latin; Computus; Medieval Mathematics